2002
DOI: 10.5713/ajas.2002.713
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Non-oxidized and Oxidized Soybean Oil Supplemented with Two Levels of Antioxidant on Broiler Performance

Abstract: A study was designed to determine the effects on broiler performance of two levels of antioxidant (ethoxyquin) in poultry rations containing two levels of oxidized and non-oxidized soybean oil. One hundred and eighty, day old broiler chicks were randomly divided into six experimental groups comprising thirty chicks on each treatment. Six experimental rations having 2% nonoxidized soybean oil, 2% and 3% oxidized soybean oil, all three supplemented with normal (125 g/t) or higher (175 g/t) level of ethoxyquin, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Malondialdehyde is a three-carbon cytotoxic molecule, produced by peroxidation of polyunsaturated fatty acids [49]. The serum concentrations of MDA, as a marker of lipid peroxidation status, have been shown to increase due to the consumption of peroxidized oil as reported in previous studies [9,14,16,30]. In the present study, serum MDA concentrations decreased with feeding with peroxidized oil when measured on day 14 and 35, and MDA levels were higher on day 35 than day 14.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Malondialdehyde is a three-carbon cytotoxic molecule, produced by peroxidation of polyunsaturated fatty acids [49]. The serum concentrations of MDA, as a marker of lipid peroxidation status, have been shown to increase due to the consumption of peroxidized oil as reported in previous studies [9,14,16,30]. In the present study, serum MDA concentrations decreased with feeding with peroxidized oil when measured on day 14 and 35, and MDA levels were higher on day 35 than day 14.…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, there may be a threshold beyond which the impact of peroxidized lipids manifests itself. The fact that detrimental effects of dietary peroxidized soybean oil was expressed more in the long term is supported by Anjum et al [14] and Lu et al [30] in broilers and pigs, respectively. DeRouchey et al [36], Liu et al [11] and Rosero et al [12] reported reductions in ADFI in pigs when feeding peroxidized lipids and these effects were dose-dependent.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…According to Lu et al (2014), the antioxidants ethoxyquin and propyl gallate, administered individually or in combination with vitamin E, were more effective than a vitamin E dose of 200 mg kg −1 . In contrast, Anjum et al (2002) and Tavarez et al (2011) did not report an improvement in the performance of broiler chickens fed diets containing rancid soybean oil supplemented with propyl gallate and ethoxyquin. Dietary stressors like oxidised feeds are a source of free radicals, which induce oxidative stress in birds (Lu et al, 2014).…”
Section: Discussionmentioning
confidence: 60%
“…The quality of oil as a source of energy in poultry diets influences growth performance and the health status of flocks. Low-quality oil added to broiler chicken diets decreases productivity (Anjum et al, 2002;McGill et al, 2011), increases mortality (Anjum et al, 2004) and decreases the quality of animal products (Zhang et al, 2011). Diets rich in polyunsaturated fatty acids (PUFAs) increase susceptibility to lipid peroxidation and decrease the antioxidant capacity of animals.…”
Section: Introductionmentioning
confidence: 99%